2000
DOI: 10.1901/jeab.2000.73-177
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Arbitrary Conditional Discriminations by Young Normally Developing Children

Abstract: Three experiments investigated conditions designed to facilitate acquisition of arbitrary conditional discriminations in 3- to 6-year-old normally developing children. In Experiment 1, 6 subjects failed to master the arbitrary match-to-sample task under conditions of differential reinforcement alone, but 7 subjects did so when instructions or instructions and sample naming were added. In Experiment 2, sample naming introduced in a blocked-trial arrangement resulted in acquisition, but only when the sample name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
4
8

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 28 publications
(40 reference statements)
4
51
4
8
Order By: Relevance
“…However, many studies have revealed that people with developmental disabilities or young children with typical development find it difficult to learn some stimulus relations through standard MTS tasks (e.g., Saunders & Spradlin, 1989;Pilgrim, Jackson, & Galizio, 2000;Doughty & Saunders, 2009). Thus, in an applied setting, there is a need to determine the variables that encourage the learning of stimulus relations in MTS tasks and develop procedures other than MTS tasks to enable individuals to learn the relations among stimuli more efficiently and effectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies have revealed that people with developmental disabilities or young children with typical development find it difficult to learn some stimulus relations through standard MTS tasks (e.g., Saunders & Spradlin, 1989;Pilgrim, Jackson, & Galizio, 2000;Doughty & Saunders, 2009). Thus, in an applied setting, there is a need to determine the variables that encourage the learning of stimulus relations in MTS tasks and develop procedures other than MTS tasks to enable individuals to learn the relations among stimuli more efficiently and effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Especifi camente em relação à população de bebês, algumas das principais difi culdades relatadas nas pesquisas sobre equivalência podem ser somadas às difi culdades enfrentadas para a realização de outras investigações experimentais com bebês (Gil & Oliveira, 2003;Gil, Oliveira, Sousa & Faleiros, 2006;Pilgrim, Jackson & Galizio, 2000;Wilkinson & McIlvane, 2001).…”
Section: T P Oliveira E M S C a Gilunclassified
“…A literatura tem ressaltado que os resultados ainda são incipientes a respeito dos parâmetros necessários para investigar tais fenômenos na referida população (Gil & Oliveira, 2003;Gil, Oliveira, Sousa & Faleiros, 2006;O'Donnell & Saunders, 2003;Pilgrim, Jackson & Galizio, 2000;Wilkinson & McIlvane, 2001).…”
Section: Discussão Geralunclassified
See 1 more Smart Citation
“…Finally, the experimenter should treat subjects with courtesy and convey gratitude for the individual's participation (Pilgrim, 1998). Pilgrim , Jackson , and Galizio (2000) reported the use of a nonautomated procedure to assess the acquisition of conditional discriminations in 3-to 6-year-old typically developing children. Experimental sessions were conducted at the children's preschool or after-school program.…”
Section: Experimental Setting and Sessionsmentioning
confidence: 99%